Imaging of HIV assembly and release - Müller, Barbara; Krijnse-Locker, Jacomine (Human retroviruses, 2014)
Assembly, release and maturation of HIV-1 particles comprise a highly dynamic sequence of events, characterized by a series of dramatic rearrangements of the viral structural proteins and overall virion architecture. HIV-1 morphogenesis is a relatively rapid and asynchronous process, showing high variability between cells and individual virions. Therefore, bulk biochemical methods are not ideally suited to study specific aspects of this process in detail. In contrast, imaging represents a direct approach to analyze individual particles and events. While live-cell imaging can reveal the dynamics of intracellular events with high temporal resolution, it falls short in revealing ultra-structural details. Thus, live-cell fluorescence microscopy and electron microscopy (EM) can complement each other to gain insight into both the dynamics of assembly and the structures detected at HIV-1 assembly sites. In this chapter we describe microscopic setups, tools, and methods for live-cell fluorescence microscopy as well as for different EM techniques, which have been successfully used by us and others to study HIV-1 assembly at the host cell plasma membrane. These methods can be used in a complementary manner to investigate the effects of cellular factors, mutations in the viral genome or antiviral drugs on dynamic and structural aspects of HIV-1 morphogenesis.
Gesehen am 17.11.2020